HUBUNGAN TINGKAT PENGGUNAAN SMARTPHONE DENGAN KEJADIAN MIOPIA - Maria H. Wea (Universitas Citra Bangsa, 2018)
The easy way offered by smartphone makes more people spend a lot of time interacted with smartphone. But behind that, many of smartphone users are not aware of the dangers which can be caused by a smartphone. Generally smartphone users used the smartphone with a close distance to the eyes and in the long term. Excessive used of smartphones will improve the power of eye accommodation, which ultimately impacts the sharp decline of vision in the form of farsightedness (myopia). This study aimed to find out the relationship between the levels of smartphone usage with the incidence of farsightedness (myopia) on nursing student’s class 7th at Citra Husada Mandiri Health Science Institute Kupang. This research design used in this research was correlational research used cross sectional research design. The sampling technique was used purposive sampling with the number of samples of 53 respondents. Data collection for dependent variable used Snellen card while independent variable used questionnaire sheet Based on the Lambda Crosstabs test results there was a significant relationship between the level of smartphone usage with the incidence of farsightedness (myopia) in nursing students class 7th at Citra Husada Mandiri Health Science Institute Kupang with p value 0,023 (p value <0,05). It was expected that the respondents and public become more aware to the myopia incidence that was derived from the usage of smartphones. Smartphone users should pay more attention to the position, the intensity of the lighting, the length of smartphone usage and the distance between the eyes with the smartphone screen. The better way to use smartphone was consider the distance between the smartphone screen with the eye was <30 cm and did not use smartphone> 4 hours continuously in one day